A Comprehensive Analysis of the Theoretical Foundations of Ecotourism Clusters Using the Delphi Method - Khushmurotov Zoyir Bektemirovich; Jumayev Sanjar Anvar o‘g‘li (Journal of Indigenous Culture, Tourism, and Language, 2026)
Purpose: The research aims to develop a theoretical framework for ecotourism clusters in regional ecological networks to address the gap in theory regarding the composition and governance of ecotourism clusters in transitional economies. While there has been rising interest in tourism clusters, few studies have systematically analyzed the key components and operational relationships of ecotourism clusters using a structured expert-based approach. Research Methodology: The study uses the Delphi method, which includes open and closed questions and interviews, with a panel of multidisciplinary experts in tourism, environmental protection, and cluster development. This expert-based approach is applied to gather insights on the components and governance of ecotourism clusters. Results: The results show a consensus that ecotourism clusters are defined as territorial, cooperative, environmental conservation-focused systems involving tourism services, local economic actors, and independent governance structures. The analysis suggests that clusters with an optimal size (12–14 members) enhance regional coordination, enable sustainable resource management, and reduce or mitigate the ecological burden of tourism. Conclusions: The research concludes that ecotourism clusters not only act as profit-maximizing networks but also serve as institutional equilibria, balancing economic growth with environmental protection. The findings provide a basis for strategic frameworks in designing sustainable regional development and policies. Limitations: The study is limited by the panel’s subjective nature, as it is based on expert opinions, which may not be fully generalizable across all contexts. Further empirical testing is needed for a broader application. Contributions: This research contributes by offering a theoretical framework for ecotourism clusters and highlighting the importance of multi-stakeholder collaboration in managing sustainable regional tourism.